An Investigation of Fruits and Vegetables Intake Among Female Adolescents of the City of Isfahan - Peyman Yarmohammadi; Parastoo Yarmohammadi (Shiraz University of Medical Sciences, 2017)
Background: A diet rich in fruits and vegetables can lower the risk of cancer, cardiovascular diseases and strokes. For adolescents, particularly females, eating enough fruits and vegetables is critical. This study intended to explore fruits and vegetables intake among the female adolescents living in the city of Isfahan, Iran. Methods: This descriptive-analytical study was performed on 331 female students, who were recruited by cluster randomized sampling. A valid self-designed questionnaire was used that covered a set of items on demographic data and amount of fruits and vegetables used by the students. This questionnaire was completed by the students in their classrooms, during school hours. Results: The average intake of fruits and vegetables by female adolescents was 3.11 servings per day. In this study, for 10.3% of the female adolescents, the intake of fruits and vegetables was 5 servings or more. For female adolescents, there was a statistically significant correlation between the consumption of fruits and vegetables and the level of education of their parents. It was also found that the intake of fruits and vegetables was positively correlated with the household's income. Conclusions: Given the standard values reported for the intake of fruits and vegetables, the findings of this study revealed that the female adolescents participating in this research were susceptible to the health risks resulting from insufficient consumption of fruits and vegetables.